Properties of solutions of half-linear elliptical systems of nondivirgent kind - Kalita , E. A. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Results on the existence of finite and infinite singular points are obtained for multilinear elliptical systems that satisfy an analogue of the Cordes condition.